PENGARUH STORE IMAGE, PRODUCT SIGNATURENESS DAN QUALITY VARIATION TERHADAP QUALITY PERCEPTION DAN PURCHASE INTENTION PRODUK PRIVATE LABEL DI HYPERMART SURABAYA - MANDASARI, YESSICA (Universitas Katolik Widya Mandala Surabaya, 2012)
The development of retail business in Surabaya the more compete in the retailers closer to its consumers, one of the way is by making a product private label. Researcher using respondents as much as 175 people at Hypermart Surabaya to fills the questionnaire. The hypothesis which is checked thoroughly is connecting the relation between store image, product signatureness, and quality variation against Quality Perception on Purchase Intention. Researcher is using Structural Equation Model (SEM) as her method to test 7 hypothesis which have been checked before. However the test result by using t-value showing that all connections between all variables in this research are proven not significant